Effect of ACEA 1021 on Neurotoxicity Induced by Dexamethasone - Initial Behavioral Study - Beata Krasuska-Grzegorczyk; Łukasz Komsta; Zofia Danilczuk (Polskie Towarzystwo Farmaceutyczne, 2024)
Considerable evidence suggests that glucocorticoids (GCs) play an important role in neurodegeneration. Chronic elevated levels of GCs can result in neuronal degeneration of the hippocampal piramidal neurons, which are paralleled by cognitive deficits. Moreover, GCs potentiate stress or ischemia-induced accumulation of excitatory amino acids (EAA) in the extracellular space of hippocampus. ACEA 1021 (licostinel), a selective antagonist of the N-methyl-D-aspartate (NMDA) receptor, has been reported to prevent the excitotoxic action of high extracellular glutamate levels. The aim of this study was to investigate the effect of ACEA 1021 on neurotoxic effect of dexamethasone (DEX - a synthetic GCs receptor agonist). The experiments were carried out on Albino Swiss mice (25-30 g). ACEA 1021, at the doses: 1.25 and 2.5 mg/kg/day, ip, was administered 15 min before DEX (16 mg/kg/day, ip). The long-term memory acquisition (passive avoidance test) and the motor performance ("chimney" test) were evaluated 14 days after the drugs administration. The prolongation of climbing time in the "chimney" test and decrease of the retention time in the memory task of mice treated with DEX for 14 days. In mice treated with DEX for 14 days, ACEA 1021 at the both doses reduced the climbing time in the "chimney" test, at the dose of 1.25 mg/kg improved memory acquisition. The above findings suggest that ACEA 1021 could prevent the neurotoxic effects induced by DEX, but further study needs to be carried out to explain this effect.